Implikasi Putusan Mahkamah Konstitusi Nomor 39/PUU-XVII/2019 tentang Pengujian Pasal 416 Ayat 1 Undang-Undang Nomor 7 Tahun 2017 tentang Pemilihan Umum Terhadap Pemilihan Presiden dan Wakil Presiden : Implications of Constitutional Court Decision No. 39/PUU-XVII/2019 on the Review of Article 416(1) of Law No. 7 of 2017 on General Elections Regarding the Election of the President and Vice President - Syaipil Azwar (SIYASI: Jurnal Trias Politica, 2024)
Article 416 Paragraph 1 of Law Number 7 of 2017 on General Elections creates legal uncertainty regarding presidential and vice-presidential eligibility criteria when only two candidate pairs participate. This article replicates Article 159 Paragraph 1 of Law Number 42 of 2008, previously annulled by the Constitutional Court through Decision Number 50/PUU-XII/2014. This research aims to analyze judicial considerations and implications of Constitutional Court Decision Number 39/PUU-XVII/2019 on presidential elections. The research employs a normative juridical approach with literature study methods. The findings show the Constitutional Court granted the petition by declaring Article 416 Paragraph 1 conditionally unconstitutional due to constitutional harm. Judges considered that vote distribution requirements of minimum 50% and 20% apply only to elections with more than two candidate pairs based on Article 6A of the 1945 Constitution interpretation. This decision provides legal certainty that when only two candidate pairs exist, the winner is determined by the most votes, thereby avoiding election repetition and constitutional harm to society.